Gold(I)/Chiral Brønsted Acid Catalyzed Enantioselective Hydroamination–Hydroarylation of Alkynes: The Effect of a Remote Hydroxyl Group on the Reactivity and Enantioselectivity. Issue 3 (24th November 2014) - Shinde, Valmik S.; Mane, Manoj V.; Vanka, Kumar; Mallick, Arijit; Patil, Nitin T.
Abstract The catalytic enantioselective hydroamination–hydroarylation of alkynes under the catalysis of (R3P)AuMe/(S)‐3, 3′‐bis(2, 4, 6‐triisopropylphenyl)‐1, 1′‐binaphthyl‐2, 2′‐diyl hydrogenphosphate ((S)‐TRIP) is reported. The alkyne was reacted with a range of pyrrole‐based aromatic amines to give pyrrole‐embedded aza‐heterocyclic scaffolds bearing a quaternary carbon center. The presence of a hydroxyl group in the alkyne tether turned out to be very crucial for obtaining products in high yields and enantioselectivities. The mechanism of enantioinduction was established by carefully performing experimental and computational studies.